Perancangan dan Analisa Antena Yagi 12 Elemen untuk Module Lora RFM95W pada Frekuensi 915 MHz - Fajar Alviandi; Koesmarijanto Ko; Hendro Darmono (Politeknik Negeri Malang, 2021)
The purpose of this research is to design a 12 element Yagi antenna so that it can be applied to the Lora RFM95W module which works at a frequency of 915 MHz, to find the effect of signal reception power on the Lora module. In this study, the implementation of the yagi antenna and built-in antenna was tested in line of sight and non-line of sight. The 12-element yagi antenna test results obtained a Return Loss of -17.8 dBm and a VSWR value of 1.29. The average gain obtained is 5.6 dB. And the results of the implementation of the LOS state for a distance of 200 meters the yagi antenna has an RSSI value of -98 dBm, while the built-in lora antenna has a power level of -109 dBm. The second test results in a Non-LOS (Wall Obstruction) state at a distance of 25 m the built-in antenna has an RSSI value of -95 dBm, while the 12 element yagi antenna is -77 dBm. The test results in Non-LOS (Tree Obstacle) at a distance of 25 m the built-in antenna has an RSSI value of -84 dBm, while the 12 element yagi antenna is -78 dBm. So that in the implementation of the 12 element yagi antenna and the built-in antenna, it can be concluded that for the RSSI data, the directional yagi antenna is better than the omnidirectional lora RFM95W antenna built-in antenna.